Infectious diseases in donkeys and mules: an overview and update - Barrandeguy, Maria Edith; Carossino, Mariano (Elsevier, 2018)
The global equine population comprises a total of 114 million equids, which includes an estimate of 44 million donkeys (Equus asinus) and 11 million mules. Donkey populations have gradually expanded throughout the globe, particularly in developing countries. In spite of their relevance in several countries around the world, the infectious diseases affecting this group of equids are largely unknown; consequently, the available information regarding infectious diseases affecting working equids is limited. The scope of this article is to provide a brief update on the most relevant infectious diseases affecting donkeys and mules worldwide.